Tropical cyclones - Synoptic methods of forecasting - RAO, A.V.R. KRISHNA (MAUSAM, 1997)
The tropical cyclone is one of the most destructive natural disasters which is capable of causing loss of life and damage to the property. Strong winds, heavy rains and storm surges associated with the cyclones, are the phenomena which are responsible for causing the damage. The issue of warnings about the impending cyclones in time help to reduce the loss of lives that the cyclone causes. To forecast its formation, structure and movement, the processes involved in its evolution and subsequent movement, are to be understood well. In this article an attempt has been made to review the literature about the cyclone characteristics and its structure. Synoptic methods of forecasting its formation and movement are also reviewed. Existing literature on their association with QBO and ENSO is also summarized. Some forecasting rules that may be of help to an operational forecaster are mentioned.